Types and Severities of Export Barriers: Evidence from Indonesian SMEs - Mohamad Dian Revindo (Institute for Economic and Social Research, 2017)
Small and Medium-sized Enterprises (SMEs) are more constrained to export than their large counterparts and SMEs' limited participation in export market is more prevalent in developing than in developed countries. Extant literature suggests that SMEs encounter a set of export inhibiting factors distinct to those faced by large firms and therefore accurate identification of export barriers is crucial in fostering SMEs export. This study investigates the export barriers faced by Indonesian SMEs. The evidences were collected from 271 exporting SMEs and 226 non-exporting SMEs in seven provinces in Jawa, Madura and Bali regions. The results show that the types and severities of export barriers perceived or encountered by SMEs vary across export stages and across products/industries. Further, export barriers can be distinguished by their general or specific nature. The policy and managerial implications of the findings are discussed.